Case report: Treatment of a patient with STEMI and cardiogenic shock caused by RCA originating from LAD - Niu, Qiang; Zhao, Yunhe; Li, Haiying; Wang, Qilei; Zhu, Haijun; Bi, Chenglong; Zhang, Hui; Wang, Jian; Cheng, Cheng; Song, Beibei; Jin, Chengwei; Lv, Ming; et al. (Frontiers in Cardiovascular Medicine, 2023)
The right coronary artery originating from the left anterior descending artery is a very rare variation of coronary artery anomaly. This kind of anomaly is usually considered to be clinically benign. Here we present an acute myocardial infarction patient with a single coronary artery, in whom the LAD and RCA are both occlusive in the same time. He suffered from ventricular fibrillation, cardiogenic shock and severe bradyarrhythmias for many times. Fortunately, this patient survived frome death through our effective medical procedures.